Is Time out of Joint? : On the Rise and Fall of the Modern Time Regime - Assmann, Aleida (Book collections on Project MUSE., 2020)
"Is, as Hamlet once feared, the time out of joint? What has happened to our relation to the past and the future? The past has returned in various shapes: as nostalgia, as traumatic impact, and as historical origin or key event for the purposes of nation building. The future, meanwhile, has lost much of its glamor, too. The notion of progress and a utopian future have been eroded a growing ecological crisis. The seemingly solid moorings of our temporal orientation have collapsed within the time span of a generation. In order to better understand our temporal crisis, we must start by reconstructing what has just disappeared. In this book, Aleida Assmann tracks the rise and fall of what she calls "the time regime of modernity," explaining what we have both gained and lost in this profound transformation of our cultural values and premises"--